A Novel Approach to Inhibit Heat Shock Response as Anticancer Strategy by Coumarine Compounds Containing Thiazole Skeleton - Koca, İrfan and Gumus, Mehmet and Ozgur, Aykut and Disli, Ali and Tutar, Yusuf (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Inhibition of the Hsp90 function is an essential therapeutic approach and several inhibitors were designed as anti-cancer agents. These inhibitors are ATPases and they aim to deregulate Hsp90 folding function. ATPase proteins are common in human metabolism but they form nonspecific targets. Hsp90 functions as dimer with coordinating chaperones. Heat Shock Organizing Protein (Hop) forms a bridge between Hsp90 and Hsp70-Hsp40 complex to form Hsp90-Hsp70 coordination. Perturbing conformational changes of these Hsp proteins, dimer formation, and protein-protein interactions inhibit Hsp90 substrate protein folding function. This approach does not target all ATPase proteins but targets Hsp90 function solely. For this purpose, we designed compounds to block Hsp90 function. Moreover, molecular docking studies as well as competition analysis of the compounds were performed with Hsp90. Novel thiazolyl coumarine compounds were determined as valuable C-terminal Hsp90 inhibitors and provide promising templates for the drug design. Anticancer activities of these novel compounds were tested by employing human colon (DLD-1) and liver cancer (HepG2) cell lines. Thiazolyl coumarine compounds are found to be significant and useful for the treatment of human colon and liver cancer as evidenced by in vitro and in silico results.
Keywords: thiazole